2012
DOI: 10.1152/ajpendo.00328.2011
|View full text |Cite
|
Sign up to set email alerts
|

Insulin detemir enhances proglucagon gene expression in the intestinal L cells via stimulating β-catenin and CREB activities

Abstract: Insulin therapy using insulin detemir (d-INS) has demonstrated weight-sparing effects compared with other insulin formulations. Mechanisms underlying these effects, however, remain largely unknown. Here we postulate that the intestinal tissues' selective preference allows d-INS to exert enhanced action on proglucagon (Gcg) expression and the production of glucagon-like peptide (GLP)-1, an incretin hormone possessing both glycemia-lowering and weight loss effects. To test this hypothesis, we used obese type 2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
5
0
1
Order By: Relevance
“…Expression of the genes of calcineurin pathway (but not CRTC-pathway) was downregulated in the presence of HC-030031. These pathways regulate the gene expression of pre-proglucagon (GCG), the precursor involved in synthesis of proglucagon-derived gut hormones and proconvertase1/3 (PCSK-1), the enzyme required for breakdown of pre-proglucagon to its derived gut hormones and their release [55][56][57]. SCFA-induced increase in expression of these genes was prevented by HC-030031.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the genes of calcineurin pathway (but not CRTC-pathway) was downregulated in the presence of HC-030031. These pathways regulate the gene expression of pre-proglucagon (GCG), the precursor involved in synthesis of proglucagon-derived gut hormones and proconvertase1/3 (PCSK-1), the enzyme required for breakdown of pre-proglucagon to its derived gut hormones and their release [55][56][57]. SCFA-induced increase in expression of these genes was prevented by HC-030031.…”
Section: Discussionmentioning
confidence: 99%
“…Although PKA is the canonical stimulator of CREB and ATF-1 phosphorylation, insulin has been shown to stimulate CREB phosphorylation in pancreatic ␤-cells and in other cell lineages (18,20). This, along with the lack of the activation of CRE element-fused luciferase reporter gene expression by GLP-1(28 -36)amide, reported recently by Liu et al (22), drove us to further investigate whether GLP-1(28 -36)amide indeed stimulates cytoplasmic cAMP levels and PKA activity.…”
Section: D and F)mentioning
confidence: 99%
“…The cAMP-related signaling pathway has been found to be involved in the proglucagon gene transcription and GLP-1 production . Liu et al have also shown that insulin stimulates the phosphorylations of β-catenin and cAMP response element-binding protein (CREB) in intestinal L cells in a phosphatidylinositol 3-kinase (PI3K)- and/or ERK MAPK-sensitive manner and then enhances proglucagon gene expression . Cell division cycle 42 (Cdc42) has been demonstrated to regulate actin remodeling, activation of ERK MAPK and Cdc42-dependent p21-activated kinase-1 (PAK1), and GLP-1 secretion in response to insulin in intestinal endocrine L cells .…”
Section: Discussionmentioning
confidence: 99%